(untitled) (International Journal of Innovative Technologies in Economy, 2022)
The paper considers the issues of post-crisis economic recovery and the impact of the Covid-19 pandemic on consumption, savings and investments. The indicators of consumption, savings and investment are studied on the example of three groups of countries. In particular, the G 7 countries, the group of countries from G 20 and the three countries of the South Caucasus. A certain synchronicity has been established between the upheavals of the early 20th and 21st centuries, which is 11 years. It is concluded that for further sustainable economic development and rapid economic recovery, it is necessary to focus on new growth drivers.